The Effect of pH on Quercetin Release from Zn Crosslinked Chitosan-Alginate Membrane and Its Kinetics - Hastuti, Budi; Nurroudhlotiningtyas, Tejayani; Hadi, Saptono; Martanisa, Mutiah (Indonesian Journal of Chemistry, 2026)
This research aims to assess the ability of Zn-crosslinked chitosan (Chi) and alginate (AG) membranes to deliver quercetin into the body by testing the release with variations in the pH of the dissolution medium. Chi-AG membrane crosslinked with Zn and loaded with quercetin to produce Chi-AG-Zn membrane with tear-resistant and elastic properties. The FTIR spectrum of the Zn crosslinked Chi-AG membrane containing quercetin shows the formation of a Chi-AG-Zn membrane with a shift in the characteristic peaks and the formation of new characteristic groups, namely Zn at a wavelength of 549 cm−1 and phenol at 1379 cm−1. SEM testing showed that the surface of the fibrous membrane and quercetin were successfully loaded. Entrapment efficiency testing yielded relatively high results, specifically 91 ± 0.08%. The release of quercetin from the Zn-crosslinked Chi-AG membrane was investigated by varying the pH of the dissolution medium, specifically at pH 1.2, 5.0, and 7.4. The results showed the highest release at pH 7.4. Membrane release follows the Korsmeyer-Peppas model, and the release mechanism is governed by Fick's diffusion. These findings suggest that the Zn-crosslinked Chi-AG membrane has potential as a pH-responsive drug delivery system for targeted release in intestinal conditions.